Computational simulation characteristics desorption in TPS aggregates; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 76 : Thermophysical Basis of Energy Technologies, Tomsk, October 10–12 2013 - Goldaev S. V. Sergey Vasilievich (2014, 2014)
Title screen